Transpedicular fixation in the treatment of various spinal disorders. - (:unkn) unknown (My University, 1993)
36 patients with 157 inserted pedicular screws are presented. The patients are evaluated in 5 different groups; group I: fractures, group II: spinal tuberculosis, group III: spinal tumours, group IV: spondylolisthesis and group V: scoliosis. The mean age and the mean follow-up of the groups are respectively 42 years and 10.8 months. Cotrel-Dubousset instrumentation (CD), Alici Instrumentation, Fixateur Interne (Dick) or Steffee plate are used to stabilize the spine. The low complication rate of pedicular screw insertion is related to the used technique.